DESIGNING ENGLISH E-MODULE THROUGH SMART APPS CREATOR FOR JUNIOR HIGH SCHOOL - Riza, Armilia; Afriyanti, Rika; Sevrika, Hevriani (Universitas Islam Nahdlatul Ulama Jepara, 2025)
The purpose of this research is to produce an Android-based e-module using Smart Apps Creator that is valid on greeting and leave taking material at SMP N in Padang City, West Sumatra. As a result, e-modules can be used as one of the English learning resources, especially greeting and leave taking materials. This type of research is research and development (R&D) with the development model proposed by Plomp (2013). The stages used in this development model are only stage 1 to stage 2, namely the initial investigation stage, prototyping phase which doubles the validity test. The research instrument used was a validity questionnaire. Based on the validator's assessment, the validity of the android-based e-module using Smart Apps Creator was 92.5% with a very valid category. Based on the research results, it can be concluded that the android-based e-module using Smart Apps Creator on greeting and leave taking material at SMP N in Padang City, West Sumatra is declared valid and can be used by teachers and students.